Structure of Mangrove Vegetation Community in the Tidal Area of Siak River, Riau - Hasan, Masyhuda; Efriyeldi, Efriyeldi; Mulyadi, Aras (Jurnal Perikanan dan Kelautan, 2025)
Global warming is one of the natural phenomena that impacts the flow of the Siak River. Among the impacts are sea level rise and seawater intrusion. These changes also affect the distribution of flora and fauna from the sea into the River. This study aims to determine the structure of mangrove vegetation communities and water quality conditions found in the tidal area of the Siak River. This research was conducted in October 2024. The research location consists of 4 stations, each station was placed in 3 plots following the flow of the River, with a distance of 100 m between each plot. Each plot has a size of 10 x 10 m. This research was conducted using the survey method. The study identified six mangrove species, consisting of 2 true mangroves and four associated mangroves. The density of mangrove vegetation in the research location is categorized as good, with the highest number of 1933.33 ind/ha at stations I and II, and the lowest at 1633.33 ind/ha at station IV. The results of the critical value index indicate that Sonneratia caseolaris plays a vital role in all research stations, with the highest percentage of 252.90% at station II and the lowest 230.20% at station I. The results of the ANOVA test analysis of density between stations showed a significant value. 0.148, which states that there is no significant difference between the four stations. Water quality measurements showed a temperature value of 28-30 °C; salinity 0 ppt, and pH 5.4-6. Sediment types at all stations were dominated by mud. The highest average organic matter was in station I, at 11.90%, while the lowest was in station II, at 6.83%. The value of Total Suspended Solid (TSS) at the study site ranged from 0.0153 to 0.1640 mg/L. Station II was dominated by muddy sand, and station III was dominated by sand with a total sediment organic matter content of 0.46-23.33%. The nitrate content found ranged from 0.0146-0.0583 mg/l, and the phosphate ranged from 0.0465-0.0996 mg/L. The linear regression test results for mangrove density with TSS, organic matter, and nutrient (nitrate and phosphate) content showed a weak relationship